A identidade do licenciado em psicologia: uma análise das regulamentações brasileiras entre 1962 e 2007 - Leticia Siqueira Lemos (2008)
Since the early 1980's, undergraduate courses in Brazil have gone through major structural reforms. A graduate training program in psychology relates to these reforms and has been debated in various forums around the country. However, in discussions on the national curriculum guidelines for courses in psychology, substantial discussions have not been held on the teacher education program, which is the graduate training for the professor of psychology, since the law 4,119 of 1962 which regulates the profession of psychologist, and it's graduate training courses. The theme of this research is the teacher education program in psychology. More specifically, the work had as object the identity of the teacher licensed in psychology. As a space object cut, the regulations of the Brazilian Education and psychology were delimited and as a time cut, the laws that were in force between 1962 and 2008. The purpose of the research was to analysis factors that cooperating with the construction of the identity of the teacher licensed of the area, from Brazilian regulations on their graduate training and performance during the period. As methodology, literature and documentary search was used, in which the regulations of the teacher education program in psychology was examined, from its use and purposes. Comparisons with other sources, such as the curriculum of the psychology courses of the Federal University of Minas Gerais (UFMG) and the grade rosters of the class of Practice of Teaching of psychology of the teacher education program in psychology of UFMG, were established in order to enrich the analysis and reconciling the results. As a result it appears that there are contradictions and delays in regulations on the rights of graduates in teacher education program in psychology. Contradictions that relate to the kind of graduate training that a teacher must take in this area, the fields and educational level of its performance, and the teachers specific knowledge of the curriculum. From the research, it was possible to see that there is no recognition of the teacher licensed as a professional by the organs of representation; ignorance by the market and by the professionals in the area themselves, about the specificities of the teacher education program and its area of activity, guaranteed by the existing rules in teaching, in particular, in Basic Education (including the Children's Education, Elementary School, High School, Technical and Vocational of Middle Level Education, Youth and Adult Education). In the research, some actions were proposed in order to initiate discussions and debates about the weaknesses that in the field of teacher education program in psychology need to be seen and overcome.